Passeios pelos bosques da confissão: as escritas de si em Confissões de Ralfo (1975), de Sérgio Sant’Anna - Gallas, Taciana (2021)
This paper aims to analyze in the literary text Confissões de Ralfo (1975), by Sérgio Sant'Anna, the genres of writing of the self and the different reading pacts that make up the narrative. The perception of these distinct genres, already exposed in the title and subtitle of the narrative, led us to research the mixture between the novel and other forms of fiction and non-fiction. Thus, we divided this research into four parts, the first one being responsible for contextualizing the Brazilian scenario of the 1970s and 1980s, the moment in which Sérgio Sant'Anna begins his literary career and the period in which the process of literary hybridity becomes more evident. It is also in this period that the so-called postmodern literature, whose manifestations mix different genres and artistic languages, assumes some prominence in the field of Brazilian literature. The second part has the purpose of presenting theoretical considerations about the genres autobiography, confessions, memoirs, testimony, autofiction, diary, and correspondence, writings of the self that are registered in the text and in the paratext of Confissões de Ralfo (1975). When we realize the insertion of these different genres in the narrative, we consider it extremely important to discuss the reading pacts, a kind of tacit contract between the author and the reader. The pacts discussed are the referential, committed to a referentiality external to the literary text, and the fictional agreement, in which the reader suspends his disbelief before the fictional text. The third part presents a careful analysis of Confissões de Ralfo (1975) based on excerpts from the literary text and the paratext. The purpose is to examine how the genres of writing of the self (fictional and nonfictional) are inscribed in this novel and, also, with the analysis, address how the pacts of reading are constructed. The last chapter, finally, discusses the parody present in the expression "imaginary autobiography", as well as in other passages of the book, and also evaluates the pastiche of the writings of the self, a resource that Sérgio Sant'Anna uses to reference the genres we analyze throughout our paper.